The patient perspective: arthritis care provided by Advanced Clinician Practitioner in Arthritis Care program-trained clinicians - Warmington K (Dove Medical Press, 2015)
Kelly Warmington,1 Carol A Kennedy,2 Katie Lundon,3 Leslie J Soever,4 Sydney C Brooks,5 Laura A Passalent,6 Rachel Shupak,7 Rayfel Schneider,8 1Learning Institute, Hospital for Sick Children, 2Musculoskeletal Health and Outcomes Research, St Michael’s Hospital, 3Continuing Professional Development, Faculty of Medicine, University of Toronto, 4University Health Network, 5Ontario Division, Arthritis Society, 6Toronto Western Hospital, 7Division of Rheumatology, St Michael's Hospital, 8Division of Rheumatology, Hospital for Sick Children, University of Toronto, Toronto, ON, Canada Objective: To assess patient satisfaction with the arthritis care services provided by graduates of the Advanced Clinician Practitioner in Arthritis Care (ACPAC) program. Materials and methods: This was a cross-sectional evaluation using a self-report questionnaire for data collection. Participants completed the Patient–Doctor Interaction Scale, modified to capture patient–practitioner interactions. Participants completed selected items from the Group Health Association of America's Consumer Satisfaction Survey, and items capturing quality of care, appropriateness of wait times, and a comparison of extended-role practitioner (ERP) services with previously received arthritis care. Results: A total of 325 patients seen by 27 ERPs from 15 institutions completed the questionnaire. Respondents were primarily adults (85%), female (72%), and living in urban areas (79%). The mean age of participants was 54 years (range 3–92 years), and 51% were not working. Patients with inflammatory (51%) and noninflammatory conditions (31%) were represented. Mean (standard deviation) Patient–Practitioner Interaction Scale subscale scores ranged from 4.50 (0.60) to 4.63 (0.48) (1 to 5 [greater satisfaction]). Overall satisfaction with the quality of care was high (4.39 [0.77]), as was satisfaction with wait times (referral to appointment, 4.27 [0.86]; in clinic, 4.24 [0.91]). Ninety-eight percent of respondents felt the arthritis care they received was comparable to or better than that previously received from other health care professionals. Conclusion: Patients were very satisfied with and amenable to arthritis care provided by graduates of the ACPAC program. Our findings provide early support for the deployment and integration of ACPAC ERPs into the Ontario health care system and should inform future evaluation at the patient level. Keywords: arthritis, physical therapists, occupational therapy, education, continuing, patient satisfaction